Pd/RHA and Pd/BPA as Eco-Friendly Heterogeneous Catalysts: Microwave-Assisted C–S Cross-Coupling Reaction in DMF - Katla, Ramesh; Katla, Rakhi; Goulart, Taís Barcelos; Rosa, Diego S.; Rosa, Gilber R. (Synlett, 2022)
First time, Pd-Rice Husk Ash (Pd/RHA) and Pd-Banana Peel Ash (Pd-BPA) were used as eco-friendly catalysts in the C–S cross-coupling reaction of 5-bromo-2,1,3-benzothiadiazole with various benzene thiols in DMF under microwave irradiation at 75 °C, 200 W (100 psi) for 15–25 min. These catalysts were produced from agro-industrial wastes, such as rice husk ash and banana peel ash. These can be recycled and reused up to five catalytic cycles without loss of catalytic efficiency.
Keywords: Pd/RHA; Pd/BPA; C–S cross-coupling; microwave; DMF; eco-friendly